Self Assessment System, Taxpayer Awareness, and Tax Sanctions Role Toward Taxpayer Compliance - Arifin, Zainal Arifin; Irzan Syahrial; Indra Karmaka (Sekolah Tingg Ilmu Ekonomi Y.A.I Jakarta - Indonesia, 2025)
The primary source of funding for government development is taxation. As a result, raising knowledge of tax reporting is crucial. This research attempts to ascertain how taxpayer awareness, tax penalties, and the self-assessment system affect taxpayer compliance. The government treasurer of taxpayers at the Indonesian Maritime Security Agency makes up the study's population. This study uses a quantitative research methodology and gathers primary data by distributing questionnaires. 65 respondents make up the sample size for this study, which employs the non-probability sampling technique. The partial least squares (PLS) technique is used in this study's data analysis, with the assistance of the smart-PLS 3.0 software. According to the study's findings, government treasurer taxpayers' compliance at the Indonesian Maritime Security Agency is not significantly impacted by the self-assessment method, taxpayer knowledge, or tax penalties. The study concludes that low tax reporting does not offset government treasurer taxpayers' already high compliance with their tax payment duties. Therefore, raising awareness is essential to preventing penalties in the form of fines for failing to file taxes. Abstrak - Pajak merupakan sumber pendapatan utama bagi pemerintah melaksanakan pembangunan. Untuk itu kesadaran melaporkan perpajakan sangat penting untuk ditingkatkan. Penelitian ini bertujuan untuk mengetahui pengaruh self-assessment system, kesadaran wajib pajak dan sanksi perpajakan terhadap kepatuhan wajib pajak. Populasi penelitian ini adalah wajib pajak bendahara pemerintah di Badan Keamanan Laut Republik Indonesia. Pendekatan penelitian ini adalah penelitian kuantitatif dengan menggunakan data primer melalui penyebaran kuesioner. Teknik penarikan sampel penelitian menggunakan teknik sampling non-probability dengan jumlah sampel sebanyak 65 responden. Teknik analisis data penelitian ini menggunakan teknik partial least square (PLS) dengan bantuan program smart-PLS 3.0. Hasil dari penelitian ini menunjukan bahwa self assessment system, kesadaran wajib pajak dan sanksi perpajakan tidak berpengaruh signifikan terhadap kepatuhan wajib pajak bendahara pemerintah di Badan Keamanan Laut Republik Indonesia. Implikasi dari penelitian ini menunjukkan bahwa kepatuhan wajib pajak bendahara pemerintah untuk melaksanakan kewajiban pembayaran pajaknya yang sudah baik tidak diimbangi dengan pelaporan perpajakan yang masih rendah. Oleh karenanya perlu bagi pimpinan untuk meningkatkan kesadaran agar terhindar dari sanksi berupa denda apabila tidak melaporkan perpajakannya.